2012
DOI: 10.1152/ajpregu.00260.2012
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic properties of the sodium sensor neurons in the rat median preoptic nucleus

Abstract: The essential role of the median preoptic nucleus (MnPO) in the integration of chemosensory information associated with the hydromineral state of the rat relies on the presence of a unique population of sodium (Na+) sensor neurons. Little is known about the intrinsic properties of these neurons; therefore, we used whole cell recordings in acute brain slices to determine the electrical fingerprints of this specific neural population of rat MnPO. The data collected from a large sample of neurons (115) indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Indeed, our laboratory previously showed that the local application of a hyperosmotic/isonatriuric stimulus (350 mOsm/kg H 2 O with mannitol; 150 m m NaCl) had no apparent effect on the excitability of the ventral MnPO neurons (Grob et al ., ; Tremblay et al ., ). The typical hypernatriuric aCSF‐induced depolarisation was considered to be the electrophysiological fingerprint of Na + sensor neurons (Voisin et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, our laboratory previously showed that the local application of a hyperosmotic/isonatriuric stimulus (350 mOsm/kg H 2 O with mannitol; 150 m m NaCl) had no apparent effect on the excitability of the ventral MnPO neurons (Grob et al ., ; Tremblay et al ., ). The typical hypernatriuric aCSF‐induced depolarisation was considered to be the electrophysiological fingerprint of Na + sensor neurons (Voisin et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The population of MnPO Na + sensor neurons was also characterised by the presence of distinct membrane rectifications in response to hyperpolarising current steps (Fig. A) (Voisin et al ., ). Our results revealed the distribution of these rectifying properties in Na + sensor neurons of the 1D and 3D groups (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been proposed that extracellular sodium ([Na + ] out ) variations are measured mainly by an atypical sodium channel, namely Na X , a recognized Na + -sensor (Hiyama et al, 2002 , 2004 ; Grob et al, 2004 ; Noda, 2006 ). Moreover, 80% of MnPO neurons express this atypical sodium channel (Voisin et al, 2012 ). Specifically, Na X channel is a Na + leak channel allowing Na + ions to pass through the membrane, and detect local variations in [Na + ] out (Tremblay et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%